2008
DOI: 10.1080/07391102.2008.10507201
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of the Ternary Complex of Rusticyanin-Cytochrome c4-Cytochrome Oxidase: An Insight to Possible H-Bond Mediated Recognition and Electron Transfer Reaction inT.ferrooxidans

Abstract: The metabolism of Thiobacillus ferrooxidans involves electron transfer from the Fe+2 ions in the extracellular environment to the terminal oxygen in the bacterial cytoplasm through a series of periplasmic proteins like Rusticyanin (RCy), Cytochrome (Cyt c4), and Cytochrome oxidase (CcO). The energy minimization and MD studies reveal the stabilization of the three redox proteins in their ternary complex through the direct and water mediated H-bonds and electrostatic interaction. The surface exposed polar residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…54, 55 No crystal or NMR structure of the rusticyanin-cytochrome c 4 complex is available; however, modeling studies revealed possible hydrogen-bond mediated recognition sites that included several water molecules that could stabilize this complex. 56, 57…”
Section: What Dictates the Specificity For The Redox Partner Proteinsmentioning
confidence: 99%
“…54, 55 No crystal or NMR structure of the rusticyanin-cytochrome c 4 complex is available; however, modeling studies revealed possible hydrogen-bond mediated recognition sites that included several water molecules that could stabilize this complex. 56, 57…”
Section: What Dictates the Specificity For The Redox Partner Proteinsmentioning
confidence: 99%
“…Large interatomic distances between H57 and the copper ion make it unlikely that all the histidines chelate the same copper ion. We hypothesize that H57 could instead play a role in the electron transfer pathway between Cyc2 and Rcy, and D58 may be involved in stabilizing the interface between Cyc2 and Rcy due to its hydrogen bonding ability (66). Therefore, this residue patch is thought to be most likely Cyc2-Rcy interface on Rcy.…”
Section: Resultsmentioning
confidence: 99%
“…1b). The periplasmic proteins Rcy and Cyc1 have previously been crystallized and characterized (87; 1), and the surface interactions at the interface between Rcy and Cyc1 have been determined (66). The Cyc2 protein (485 amino acids, MW 52.4 kDa, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation is hindering postulation of a valid model for the specific binding surfaces of respirasomes. However, a working model of binding interaction between RcY and Cyc1 has been proposed by Mukhopadhyay et al, who showed that water molecules are implicated in transferring electrons from RcY to Cyc1 [17][18][19]. It is intriguing to note that, despite more than 40 years of research, the structural features of Cyc2 and its interactions with RcY are poorly understood.…”
Section: Introductionmentioning
confidence: 99%